Nested Variant of Urothelial Carcinoma Is a Luminal Bladder Tumor With Distinct Coexpression of the Basal Marker Cytokeratin 5/6. Issue 4 (29th October 2020) - Johnson, Steven M; Khararjian, Armen; Legesse, Teklu B; Khani, Francesca; Robinson, Brian D; Epstein, Jonathan I; Wobker, Sara E
Abstract: Objectives: The nested variant of urothelial carcinoma (NVUC) is a rare bladder tumor that may possess a luminal molecular phenotype. We sought to determine whether a small immunohistochemical (IHC) panel using common surrogates for molecular phenotypes would reliably classify a cohort of pure NVUC cases. Methods: IHC staining with a panel composed of markers for basal subtypes (CK5/6, CK14) and luminal subtypes (FOXA1, GATA3) was performed on pure small NVUC cases (n = 23) and 5 large NVUC cases (n = 5). Scoring of IHC stains was performed semiquantitatively. Individual cases were analyzed using previously reported IHC-based surrogates for molecular subtype. Results: The phenotype of NVUC was classified as luminal from 60.1% (FOXA1+/CK5/6−) to 100% (GATA3+/CK14−) of cases using composite phenotypes. No cases possessed a basal or squamous cell carcinoma–like phenotype. The majority of small NVUC cases (69.5%) showed subset CK5/6 expression distinctly localized to the basal layers of tumor cell nests. Intratumoral heterogeneity was also noted in CK5/6 (21.7% of small NVUC cases) but no other markers. Conclusions: NVUC appears to express markers of both basal and luminal bladder tumors. Definitive gene expression profiling may be valuable to further characterize this unique histologic variant.